2015
DOI: 10.1371/journal.pone.0143317
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Client-Perpetrated Violence against Female Sex Workers in 13 Mexican Cities

Abstract: BackgroundGlobally, client-perpetrated violence against female sex workers (FSWs) has been associated with multiple health-related harms, including high-risk sexual behavior and increased exposure to HIV/STIs. This study examined correlates of client-perpetrated sexual, physical, and economic violence (e.g., robbery) against FSWs in 13 cities throughout Mexico.MethodsFSWs (N = 1,089) who were enrolled in a brief, evidence-based, sexual risk reduction intervention for FSWs (Mujer Segura) were interviewed about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
43
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 73 publications
10
43
1
3
Order By: Relevance
“…Intimate partner violence is defined as “behaviors within an intimate relationship that cause physical, sexual or psychological harm, including acts of physical aggression, sexual coercion, psychological abuse and controlling behaviors” (World Health Organization, 2010, p11). Female sex workers (FSWs) comprise a vulnerable population who can be victimized by violence either from their stable partners (e.g., husbands, or long-term commercial partners) (Zhang et al, 2012) or from clients (Semple et al, 2015). Other than increasing vulnerability to HIV infection (Ulibarri et al, 2010), unwanted pregnancy (Silverman, Gupta, Decker, Kapur, & Raj, 2007), and physical injury (Antai, 2011), violence often causes adverse health consequences, including mental health problems (e.g., depression, loneliness, and suicidal behavior) among FSWs (Hong, Zhang, Li, Liu, & Zhou, 2013; O’Campo, Woods, Jones, Dienemann, & Campbell, 2006; Ouellet-Morin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Intimate partner violence is defined as “behaviors within an intimate relationship that cause physical, sexual or psychological harm, including acts of physical aggression, sexual coercion, psychological abuse and controlling behaviors” (World Health Organization, 2010, p11). Female sex workers (FSWs) comprise a vulnerable population who can be victimized by violence either from their stable partners (e.g., husbands, or long-term commercial partners) (Zhang et al, 2012) or from clients (Semple et al, 2015). Other than increasing vulnerability to HIV infection (Ulibarri et al, 2010), unwanted pregnancy (Silverman, Gupta, Decker, Kapur, & Raj, 2007), and physical injury (Antai, 2011), violence often causes adverse health consequences, including mental health problems (e.g., depression, loneliness, and suicidal behavior) among FSWs (Hong, Zhang, Li, Liu, & Zhou, 2013; O’Campo, Woods, Jones, Dienemann, & Campbell, 2006; Ouellet-Morin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These quotes highlight that aggressive clients contribute to both workers' perception of, and lived experiences with physical danger. Moreover, they correspond with existing studies on violence against sex workers in the USA, Canada, the UK, and Australia, which report that 40% to 82% of sex workers have been physically or sexually assaulted by an aggressive client (Valera, Sawyer & Schiraldi 2001;Raphael & Shapiro, 2004;Shannon et al, 2009;Semple et al, 2015).…”
Section: Physical Dangersupporting
confidence: 86%
“…Although the results of this study indicated that there were many benefits to working in the sex industry, there were also challenges and risks. Consistent with the literature, the students in this study reported that sex work left them vulnerable to violence (Haeger & Deil-Amen, 2010;Raphael & Shapiro, 2004;Shannon et al, 2009;Semple et al, 2015). While participants cited taking numerous precautions to ensure their safety, physical danger was still emphasized as a major perceived and realized risk to working in the sex industry.…”
Section: Chapter 9: Conclusionsupporting
confidence: 79%
“…Globally, client-perpetrated violence against FSWs has been associated with multiple healthrelated harms, including high-risk sexual behavior and increased exposure to HIV/STIs. They are often exposed to work-related traumas in the form of sexual, physical, and economic violence perpetrated by clients (Semple, et al, 2015).These women, who engage in the provision of sexual services for commercial consideration, put themselves at special risk of health problems for a variety of reasons. They are subject to considerable risks of physical abuse, including beatings and rape.…”
Section: Literature Reviewmentioning
confidence: 99%